Coping with Crises : Policies to Protect Employment and Earnings - Paci, Pierella; Revenga, Ana; Rijkers, Bob (Oxford University Press on behalf of the World Bank, 2013)
The continuing failure of many countries to adequately mitigate the adverse labor market impacts of economic downturns is of concern, since labor market volatility can exacerbate poverty and stunt growth. This article aims to identify potentially effective policies responses to crises by navigating the potential tradeoffs between offsetting adverse short-term impacts of economic downturns on the quantity and quality of jobs, and preserving incentives for economic recovery. The authors propose a taxonomy that categorizes interventions depending on whether they mitigate the negative short-term impact of crises or whether they stimulate recovery. The taxonomy helps policymakers to identify “win–win” policies that avoid potential tradeoffs between these objectives by simultaneously serving both. Common elements of effective interventions are feasibility, flexibility (for example the capacity for scaling up and down), and incentive compatibility—and there is no substitute for being prepared. Having sound safety nets in place before a crisis is superior to haphazardly implementing responses after a crisis hits.